A CROSS-SECTIONAL STUDY ON INDIVIDUAL FACTORS ASSOCIATED WITH SELF-MEDICATION AMONG ADULTS AGED 18 TO 50 YEARS ATTENDING HENROB HOSPITAL ZANA. - Namagembe, Zaliika; Namubiru, Rebecca; Nalubega, Jane Frank; Nansereko, Hasifa; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2025)
Background. Self-medication is becoming increasingly common among adults in Uganda. Despite its potential risks at the individual and community level, not enough studies have been done in Uganda on self-medication. This study examined individual factors associated with self-medication among adults aged 18 to 50 years attending Henrob Hospital Zana. Methodology. A cross-sectional study was conducted targeting adults attending Henrob Hospital. A total of 40 respondents were systematically selected and interviewed using a semi-structured questionnaire. The outcome variable was the medication with or without a prescription from a doctor / medical worker. The information was manually tallied, and scientific measures were used to analyze the recorded information. Thereafter, Microsoft Word and Excel programs were employed, followed by presentation in the form of frequency tables, graphs, and figures like pie charts and bar graphs. Results. The majority of respondents were males 21(52.5%),24 (60%) were in the age group of 45-50 years, 26 (65 %) of the participants replied Yes to having used any drug for self-treatment, 16 (40%) reported being busy with daily programs, respondents who reported buying medicine without a prescription from the doctor majority were Christians 21(52.5), 22 (55%) of the respondents knew the dosage of drugs by enquiring from the seller and 26 (65%) of the respondents obtained their drugs from a community pharmacy. Conclusion. Self-medication in adults is associated with age, level of education, accessibility to pharmacies, occupation, and marital status. Recommendations. Ministry of Health and other responsible bodies, including the health workers, should strive to increase the knowledge of patients about the importance of reporting and obtaining medical consultation.